A brave new world: embracing sexuality in advertising for apparel. Issue 1 (18th June 2020) - Kordrostami, Elika; Kordrostami, Melika
Abstract : Purpose: In light of the recent shift in the US culture, this paper investigates the effectiveness of female sexual empowerment as ad appeal in the apparel industry. Design/methodology/approach: Study 1 aimed to understand consumers' reactions to female sexual empowerment in ads in terms of their attitudes toward the ad, attitudes toward the brand and purchase intention. Study 2 investigated the role of gender in perceptions of female sexual empowerment in ads. Findings: This research establishes that consumers display positive attitudes toward female sexual empowerment in the apparel advertisement. These attitudes positively influence attitudes toward the brand, which in turn improve purchase intention. These effects are stronger for women than men. Research limitations/implications: This research borrows from social power theory to reveal the impact of female sexual empowerment in ads in the apparel industry. Based on the theory of planned behavior, the findings also show that female sexual empowerment can have a positive impact on purchase intention through a serial mediation of attitude toward the ad and brand. Practical implications: Marketers need to be aware of the impact of female sexual empowerment as ad appeal. Specifically, firms in the apparel industry could benefit from the positive effects of incorporating female sexual empowerment in their campaigns. Originality/value: This research is the first to investigate the role of female sexual empowerment as ad appeal in improving consumers' responses to ads.